METHODS OF ASSESSING TERRORIST THREATS TO STRATEGIC FACILITIES OF THE STATE - Azarenko, O.; Honcharenko, Yu.; Diviziniuk, M.; Shevchenko, R.; Shevchenko, O. (Municipal economy of cities. Series: «Economy science», 2023)
The study highlights the main regularities of preparation and execution of a terrorist act from the standpoint of considering a terrorist emergency as a spatiotemporal process. It is proposed to use the expert method of scenarios to assess terrorist threats to strategic objects. Ensuring the national security of Ukraine is a multifaceted problem, which includes military and political, economic and informational security, protection of the state border, and civil defence. Solving these component tasks is impossible without taking into account the possible terrorist impact on the strategic objects of the state, which include critical infrastructure enterprises, key transport communications, and military facilities. The description of any emergency requires a clear definition of the type of catastrophic event that caused it. Terrorist threats at protected strategic objects are possible socially dangerous consequences of malicious actions, i.e., terrorist acts that lead to stopping or limiting the functioning of these objects. The scenario method involves the creation of scenario development technologies that provide a higher probability of developing an effective solution. Scenarios are a set of equally compelling stories, each describing one of the potentially possible options for the future. Intrusion scenarios used in physical protection systems of protected objects consist of two parts. The first one provides a set of variants of terrorist threats, that is, expected actions of intruders against the protected object. The second is an action plan (reaction to the actions of intruders) of the physical protection system to neutralise terrorists. The process of improving the technology of developing scenarios of terrorist threats will provide a higher probability of developing an effective solution to ensure the security of strategic objects and counter terrorist threats, when possible, and a higher probability of reducing expected losses to a minimum in situations where losses are unavoidable.